Determination of trace amounts of Ag (I) in waste water samples by a novel potentiometric sensor based on perphenazine as an ionophore - Zohreh Doroudi (سلامت و محیط, 2020)
Background and Objective: Silver is a toxic heavy metal that is used in various industries and has adverse effects on both human health and the environment. In this respect its determination with sensitive and economic analytical methods is of great importance. Materials and Methods: In this research, a novel ion selective electrode based on perphenazine as an ionophore was developed for determination of Ag+. The optimum composition that showed the highest sensitivity was constructed by mixing 9% ionophore, 2% NaTPB as ionic additive, 59% DOP as the plasticizer and 30% PVC. Results: The designed sensor showed a linear response over the concentration range of 1×10-6-1×10-2 M with the slope of 60.3 mV/Decade. The detection limit of the electrode was obtained 9×10-7 M. The response time and lifetime of the proposed sensor were 5 seconds and 10 weeks, respectively. The selectivity of electrode was evaluated by matched potential method and no serious interference was observed. Conclusion: In the end, the sensor applicability in determination of Ag+ in three waste water specimens as real samples was evaluated and the good agreement between the results of sensor and the results of flame atomic absorption spectroscopy showed the designed electrode has enough accuracy and it can be used for determination of Ag (I) in the aqueous environmental samples. In conclusion, finally the performance of the prepared sensor in determining the amount of silver ions in three effluent samples was evaluated as the real samples. The results were in good agreement with those obtained by flame atomic absorption method which indicates that the designed sensor can be successfully employed in the accurate determination of silver (I) in environmental aqueous samples.